The Effectiveness of the Supervision in Preventing Irregularities in State Finances Management Implementation by the East Java Regional Police - Sutardjo,; Abrianto, Bagus Oktafian; Nugraha, Xavier; Nugraha, Xavier; Insiyah, Sayyidatul (International Journal of Psychosocial Rehabilitation, 2020)
State finance as an instrument of economic policy for the government has a very central role in the administration of the state. Unfortunately, the management of state finance has not been matched with optimal oversight. As the result, there are many cases of misappropriation of the management of state finances. One of the example is related to a village fund corruption case. Village funds are funds sourced from the APBN that are transferred through the APBD and in the form of the APBDes. In its implementation, there are many vilages funds that have not been used optimally and in accordance with its planning. Referring to these problems, the problem of this paper is 1} what is the ratio legis in overseeing the management of the state finance?; and 2) how effective is the supervision of the East Java Regional police to the management of the state finance in East Java? This research is a normative legal research using a statute approach and conceptual approach. The results of this paper are that the state finances actually as an instrument of a state policy has a very important role for the sustainability of a government. Therefore, it is necessary to supervise the management of the budget in order to ensure the use of village funds in accordance with predetermined plans. Furthermore, supervision of state financial management conducted by the East Java Regional Police in fact still cannot be said to have been effective. It is proven that there are still many corruption cases of the village funds in various villages government in Indonesia